Ikääntyvät työelämässä. Päihittääkö nuoruus ja koulutus aikuisuuden ja kokemuksen? - Ruoholinna, Tarita (fi=Turun yliopisto|en=University of Turku|, 2009)
The Ageing in Working Life. Do Adolescence and Schooling Beat Adulthood and Experience? This study examines the changes in the work and the work organisations of employees in the fields of health care and retail trade who have turned 45 and their experience of change. In addition, the question of how ageing employees experience their status in post-modern working life is explored. Attention is also focused on the choices and decisions connected with staying at work and retiring. These views are examined in relation to professions and professional cultures. Thematic interviews (N=98) were used to gather the material. The effects of the market liberalistic turn in welfare policy are clearly seen in the everyday work of the health care professions. These changes were examined from the point of view of managing by outcomes and quality assurance, multi-professional cooperation, flexibility in the division of labour, and the spread of market-like procedures. The discourse of those in involved retail trade was dominated by extremely tight global market competition and control of outcomes, and by the structural changes taking place in the retail trade sector. This change discourse was to a large extent a reaction to those changes in the functional environment which were experienced as negative and to the conflict between their own professional identity and professional ethics on the one hand, and their functional environment on the other. There were also obstacles connected with professional culture: defending one's own station and power, guarding the 'frontier', showed up in attitudes towards new management and organisation models or towards structural and functional reforms. The deep structures of professional culture and the mindset of the actors change much more slowly than the functional practices of organisations. For those in a supervisory position, the loss of power due to becoming part of a chain or because of the introduction of a team organisation model was not an easy thing to accept. The nurses and others in related fields felt that they were forced to do work that was below their level of training and professional skill. For sales personnel and those who did assisting work in health care, power and the possibility of having an influence were not so important, as long as they were able to do their work in their own way and were trusted. This view is often completely forgotten, for example, in various organisation models in which power and the possibility of having an influence entwined with power are taken for granted as being clearly positive and desired aspects of job satisfaction. Up to date professional skills were experienced as being important from the point of view of professional identity and self-worth. Thus, training can be understood as a moral obligation, which in turn is intertwined with professional ideology. In the rhetoric of adult education, an adult is expected to be an active player who will seek training again and again if working life so requires. The dark side of this ideology, which leads to feelings of guilt, was apparent in the thoughts of the respondents. Am I never good enough at my job; why must I continually strive for better, additional qualifications? The majority of the respondents evaluated their expertise as being at quite a high level. This self-confidence did not extend to applying for a job. Job recruitment was seen as a situation in which age discrimination reached its peak. The interviewees were unanimous about the idea that society favours the young. Especially among those in the retail trade sector, there was a feeling that it would be difficult, if not impossible, to find a new job of the same level or a permanent post if they were made redundant. Age discrimination was also apparent in the retail trade field in the form of older employees being retired against their will or transferred to other tasks. It was felt that ruthless forced retirement of older workers was part of the personnel policy of some organisations. The importance of one's outward appearance was connected with the theme of discrimination. This phenomenon is described using the concept of the double standard of ageing in feminist research. An ageing woman is relegated to an inferior position due to both her age and her sex. A culture that would both make possible and allow various types of choices regardless of age, which is described as being characteristic of the post-modern era, does not seem to be very topical in the practice of working life. It is important for employees that the management and the personnel policy that is being implemented makes them feel like both their contribution and they as individuals are appreciated, that their opinions are listened to and that they are noticed as persons. The interviewees hoped for gratitude and a concern for the well-being of employees that shows in everyday life. They valued training and activities aimed at maintaining their work ability, but thought that better coping at work and a pleasant working environment cannot be achieved through such measures as along as the foundation is 'in a mess'. Development of the quality of working life is the only thing that can improve job satisfaction and get people to remain in the work force longer than at present. There should be a sufficient number of properly trained employees at the work place. It was important to the respondents that they be able to stay on their job to the end with honour, since compromising with their own quality standards or acting contrary to their ideal self-image in terms of professional ethics would strike a blow to their professional self-esteem. They called for the development of various types of workplace flexibility, and felt that they have the right to a lightened workload and to early retirement. Early retirement was even seen as an altruistic deed: it would free up a place for younger workers. Thoughts of retirements were explained by familiar factors such as health and finances, life situation, the enticement of free-time, as well as by various factors related to work. It is very important to ageing employees that their work has meaningful content. The values related to self-fulfilment are felt to be of great importance, and if they cannot be realised at work, the respondents wanted more free time, either through retirement or in the form of flexibility in working life.

Tutkimuksessa tarkastellaan terveydenhuolto- ja kaupanalan 45 vuotta täyttäneiden työntekijöiden työssä ja työorganisaatioissa tapahtuneita muutoksia sekä heidän muutoskokemuksiaan. Lisäksi kysytään, millaiseksi ikääntyvät työntekijät kokevat asemansa jälkimodernissa työelämässä. Mielenkiinto kohdistuu myös työssä pysymistä ja siitä lähtemistä koskeviin valintoihin ja päätöksiin. Näkemyksiä peilataan suhteessa ammattiin ja ammattikulttuuriin. Aineiston kokoamisen metodina on käytetty teemahaastattelua (N=98). Hyvinvointipolitiikan markkinaliberalistisen käänteen vaikutukset näkyvät selvästi terveydenhuoltotyön arjessa. Muutoksia tarkasteltiin tulosjohtamisen ja laatujärjestelmien, moniammatillisen yhteistyön, työnjaon joustavoittamisen ja markkinamaisten toimintatapojen yleistymisen näkökulmista. Kaupanväen muutospuhetta hallitsivat äärimmilleen kiristynyt globaali markkinakilpailu ja tuloskontrolli sekä kaupan rakennemuutos. Muutospuhe oli pitkälti vastapuhetta negatiiviseksi koettua toimintaympäristön muutosta sekä oman ammatti-identiteetin ja -etiikan ja toimintaympäristön välistä ristiriitaa kohtaan. Myös ammattikulttuuriset esteet: oman aseman ja vallan puolustaminen, ”reviirirajojen” vartiointi näkyvät siinä, miten uudenlaisiin johtamis- ja organisaatiomalleihin sekä rakenteellisiin ja toiminnallisin uudistuksiin suhtauduttiin. Ammattikulttuuriset syvärakenteet ja toimijoiden ajattelutavat muuttuvat paljon hitaammin kuin organisatoriset toimintakäytännöt. Kaupan esimiehille vallan menettäminen ketjuuntumisen ja tiimiorganisaatisoitumisen myötä ei ollut aivan helppo asia. Sairaanhoitajat ja heidän lähiammattilaisensa kokivat, että he joutuvat tekemään koulutukseensa ja ammattitaitoonsa nähden toisarvoisia töitä. Kaupan myyjätason ja terveydenhuollon avustava henkilökunta ei valtaa ja vaikutusmahdollisuuksia niin kaivannutkaan, vaan heille riittäisi se, että he saavat tehdä työtä omalla tavallaan, heihin luotetaan. Tällainen näkemys tuntuu usein tyystin unohtuvan, kun esim. erilaisissa organisaatiomalleissa vallan ja siihen kietoutuvien vaikutusmahdollisuuksien jakamista pidetään itsestään selvästi positiivisena ja tavoiteltavana asiana. Ajantasainen ammattitaito koettiin tärkeäksi ammatti-identiteetin ja itsetunnon kannalta. Kouluttautumisen voi siis ymmärtää myös moraalisena velvoitteena, mikä puolestaan kietoutuu professioideologiaan. Aikuiskoulutuksen retoriikassa aikuisen edellyte¬tään olevan aktiivinen toimija, joka kouluttautuu yhä uudelleen, jos työelämän muutokset sitä edellyttävät. Ideologiaan kääntöpuolena sisältyvä syyllistävä vaiku¬tus näkyi haastateltavien ajatuksissa. Eikö koskaan ole riittävän hyvä työhönsä, miksi koko ajan pitäisi hankkia jotakin ylimääräistä lisäpätevyyt¬tä? Suuri osa haastateltavista arvotti osaamisensa hyvin korkealle. Itseluottamus ei yltänyt työnhakuun asti. Rekrytointi koettiin tilanteena, jossa ikäsyrjintä kulminoituu. Haastateltavat olivat yksimielisiä siitä, että yhteiskunnassa suositaan nuoria ja etenkin kaupan väki oli varsin vakuuttunut siitä, että uutta, ainakaan vastaavantasoista tai vakituista työpaikkaa olisi vaikea, ellei mahdoton löytää. Kaupassa ikäsyrjintä näkyi myös siinä, että vanhempaa väkeä oli siirretty vastentahtoisesti eläkkeelle tai toisiin tehtäviin. Iäkkäämpien työntekijöiden säälimättömän eläkkeellepanon koettiin kuuluvan joidenkin organisaatioiden henkilöstöpolitiikkaan. Syrjintään yhdistyi ajatus ulkonäön merkityksestä. Ilmiötä on feministisessä tutkimuksessa kuvattu vanhenemisen kaksoisstandardin käsitteellä. Ikääntyvä nainen asettuu niin ikänsä kuin sukupuolensakin kautta alisteiseen asemaan. Jälkimodernille ajalle ominaiseksi luonnehdittu kulttuuri, joka mahdollistaisi ja sallisi erityyppiset valinnat iästä riippumatta, ei vaikuta tämän tutkimuksen valossa työelämän käytännöissä kovin ajankohtaiselta. Työntekijöille olisi tärkeää, että johto ja harjoitettu henkilöstöpolitiikka saisi heidät tuntemaan, että heitä ja heidän työpanostaan arvostetaan, heidän mielipiteitään kuunnellaan ja heidät huomioidaan yksilöinä. Haastateltavat kaipasivat kiitosta ja arkipäivässä näkyvää välittämistä työntekijän hyvinvoinnista. He arvostivat tarjottua tyky-toimintaa ja koulutusta, mutta parempaa jaksamista ja työssä viihtymistä ei niillä voida saavuttaa, kun perusta on ”rempallaan”. Vain työelämän laadun kehittäminen voi parantaa työtyytyväisyyttä ja saada sitä kautta ihmiset viihtymään työssään nykyistä pidempään. Työssä pitäisi olla riittävä määrä oikealla tavalla koulutettua henkilökuntaa. Haastateltaville oli tärkeää, että he pystyisivät hoitamaan työnsä kunnialla loppuun saakka, sillä omista totutuista laatuvaatimuksista tinkiminen, ammattieettisen minäihanteen vastaisesti toimiminen aiheuttaisi kolhuja ammatilliselle itsetunnolle. He peräänkuuluttivat erilaisten työelämän joustomahdollisuuksien kehittämistä ja kokivat, että heillä on oikeus keventää työtaakkansa tai jäädä eläkkeelle aiemmin. Varhaisempi eläköityminen nähtiin jopa altruistisena tekona: näin vapautuu paikka nuoremmalle. Eläkeajatuksia selittivät tutusti terveydelliset ja taloudelliset seikat, elämäntilanne, vapaa-ajan kiehtovuus sekä vahvasti myös erilaiset työhön liittyvät tekijät. Ikääntyville työntekijöille on erittäin tärkeää se, että työ tuntuu sisällöllisesti mielekkäältä. Itsensä toteuttamiseen liittyvät arvot koetaan tärkeiksi ja jos niitä ei kyetä realisoimaan työssä, toivotaan enemmän vapaa-aikaa, joko eläkkeen tai työelämän joustojen muodossa.